Retratos da EJA na Amazônia Marajoara: desafios do ensino da língua inglesa na educação escolar quilombola - RIBEIRO, Karley dos Reis (Universidade Federal do Pará, 2021)
The current study aimed to discuss the teaching of the English Language (EL) for students of Youth and Adult Education (EJA) from the perspective of Quilombola School Education (EEQ) in a quilombola school at Salvaterracity, in the Marajoara Amazon. The research analyzed the teaching of LI and its consequences for EEQ, allowing to highlight other perspectives for language teaching. We used interpretative analysis and specialized bibliography of the area. The researchis of a qualitative nature and of na interpretative nature, and the theoretical contributions that supported the data analysis were: Pennycook (1998), Rajagopalan (2003), Moita Lopes (2002; 2005), and anothers. The results of the research showed that the ethno-racial issues in the classes of EL in the EEQ EJA is a challenging field to reach the quality of the teaching of EL in the EEQ proposal. The need for continuing education of IL teachers for ethnic-racial relations is na emergency need, as the data indicated that the challenges are mostly associated with the pedagogical practices of the EL teacher.